Unlock the potential for Saudi Arabian higher education: a systematic review of the benefits of ChatGPT - Faisal, Eman (Frontiers in Education, 2024)
This systematic review investigates the potential benefits of integrating ChatGPT in higher education. Focusing on ChatGPT's impact, the study identifies themes such as ChatGPT's role in teaching and instruction, enhancing student learning and engagement, aiding language learning, and promoting inclusivity. The review underscores ChatGPT's ability to reshape the educational landscape, improve research and writing, bridge language gaps, and address specific challenges. ChatGPT emerges as a transformative tool empowering educators and students, aligning with Saudi Arabia's pursuit of academic excellence and future workforce readiness.